2013
DOI: 10.1103/physreva.87.053609
|View full text |Cite
|
Sign up to set email alerts
|

Chiralf-wave topological superfluid in triangular optical lattices

Abstract: We demonstrate that an exotically chiral f -wave topological superfluid can be induced in coldfermionic-atom triangular optical lattices through the laser-field-generated effective non-Abelian gauge field, controllable Zeeman fields and s-wave Feshbach resonance. We find that the chiral f -wave topological superfluid is characterized by three gapless Majorana edge states located on the boundary of the system. More interestingly, these Majorana edge states degenerate into one Majorana fermion bound to each vort… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In the same context, Hung et al [21] found that frustrated Cooper pairing in the p-orbital bands in triangular lattice with ultracold spinless fermions exhibits an unconventional supersolid state with the f -wave symmetry. Likewise, a chiral f -wave topological superfluid can be induced in cold fermionic-atom optical lattices through the laser-field-generated effective non-Abelian gauge field, controllable Zeeman fields and s-wave Feshbach resonance [22].…”
Section: Introductionmentioning
confidence: 99%
“…In the same context, Hung et al [21] found that frustrated Cooper pairing in the p-orbital bands in triangular lattice with ultracold spinless fermions exhibits an unconventional supersolid state with the f -wave symmetry. Likewise, a chiral f -wave topological superfluid can be induced in cold fermionic-atom optical lattices through the laser-field-generated effective non-Abelian gauge field, controllable Zeeman fields and s-wave Feshbach resonance [22].…”
Section: Introductionmentioning
confidence: 99%
“…For fermions, however, it is still a big challenge to realize superfluid states with chiral odd-frequency orders because the atom loss is strong near the Feshbach resonance in high-frequency channels [24]. Theoretically, thanks to the Rashba spin-orbital couplings, the topological superfluids of fermions with chiral odd-frequency orders have been proposed to emerge in the s-wave channel of the Feshbach resonance [25][26][27][28]. In comparison with the well-studied chiral odd-frequency superfluids of fermions, the superfluids of fermions with chiral even-frequency orders are rarely studied, and only some candidate materials are proposed to have the chiral even-frequency orders due to the OPEN ACCESS RECEIVED…”
mentioning
confidence: 99%
“…Theoretically, thanks to the Rashba spin-orbital couplings, the topological superfluids of fermions with chiral odd-frequency orders have been proposed to emerge in s-wave channel of the Feshbach resonance. [25][26][27][28] . In comparison with well-studied chiral odd-frequency superfluids of fermions, the superfluids of fermions with chiral even-frequency orders are rarely studied, and only some candidate materials are proposed to have the chiral even-frequency orders due to the unconventional superconducting pairing in condensed-matter systems [29][30][31][32] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the development of laser and ultracold atom techniques gives rise to various optical lattices in which ultracold Fermi atoms can be trapped to simulate the phenomena in condensed-matter systems [7][8][9][10][11][12][13] , such as the topological Mott insulator 14 (MI) and superfluid (SF)-MI transition 15,16 . More significantly, in a laser field with a specific configuration, the trapped ultracold atoms can feel effective Abelian or non-Abelian gauge fields 17,18 .…”
Section: Introductionmentioning
confidence: 99%